A SYSTEMIC ANALYSIS MODEL FOR THE ENVIRONMENTCOMPONENTS IN METAL MINING AREAS (PANGEEA, 2025)
The impact that mining activities and capitalization of nonferrous metal ores have on the environmental conditions cannot be addressed sequentially, but only as a whole, thus leading to a system-type approach of the phenomenon. From this perspective, the entire objective reality of a hydrographic basin, taken as a whole, is considered to be a vast system that behaves like an entity and whose dynamics is controlled by the laws that govern the functionality and stability of systems.